(y2-y-2/5y)(10y/y+1)=(y2-y-2)(10y)/(5y)(y+1)

Simple and best practice solution for (y2-y-2/5y)(10y/y+1)=(y2-y-2)(10y)/(5y)(y+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y2-y-2/5y)(10y/y+1)=(y2-y-2)(10y)/(5y)(y+1) equation:



(y2-y-2/5y)(10y/y+1)=(y2-y-2)(10y)/(5y)(y+1)
We move all terms to the left:
(y2-y-2/5y)(10y/y+1)-((y2-y-2)(10y)/(5y)(y+1))=0
We can not solve this equation

You can always share this solution

See similar equations:

| 8^-6k-7=8^k+7 | | 0.04(12)+0.01m=0.02(12+m) | | 3*t+5=2 | | -1-4+b=-4+2b | | –2m=8?m | | 2r+6=10r-10-6r | | 8x-3x+4=-5x+4 | | -4-5g=-4g+6 | | 6=8+(p)/(4) | | 6-7x=-2x+8-3 | | -8m+9=-6m-7 | | 14+x=5x | | 4n+9=-15 | | 110°+3x+11=16x+4 | | -1/3-g=1/3 | | -9f+5+1=9-10f | | p=p-11 | | -2w+10=2w-10 | | x3=-48 | | -10-2j=-4j+8+8j | | 3c+5=4c-1 | | 2(3k+5)=9k-3(k+4)-1 | | 5x+1+x-9=9x-80 | | -2-5b=-3b | | | | Y=3x-9x-27x | | 4x+34=1-6 | | Y=x2-225 | | 12x+3+7x-2=90 | | 7p/10+9=15 | | 2.5x=5x+3 | | 7r-15=2r+10 |

Equations solver categories